2022
DOI: 10.1097/bpo.0000000000002244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Information About Osteochondritis Dissecans Shared Across Social Media Platforms

Abstract: Background: With the rise of social media, patients are using a variety of online resources to gather information about medical conditions and connect with others for support. Osteochondritis dissecans (OCD) occurs most commonly among children and adolescents, necessitating early diagnosis and management. The purpose of this study is to evaluate content on social media about OCD to quantify the reach of information shared and themes of discussion surrounding this condition. Methods: A search was performed acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…There is evidence that active preoperative patient education improves postoperative outcomes in spinal surgery regarding emergency room use, expenditure, and psychological measures [ 17 , 18 ]. Given that social media websites have been established as poor sources of information, the high proportion of patients utilizing these websites is concerning and offers room for advancement [ 15 , 19 , 20 ]. Our study revealed that most information provided originates from nonacademic, nongovernment sources (72.2%), with 21.5% from social media websites.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that active preoperative patient education improves postoperative outcomes in spinal surgery regarding emergency room use, expenditure, and psychological measures [ 17 , 18 ]. Given that social media websites have been established as poor sources of information, the high proportion of patients utilizing these websites is concerning and offers room for advancement [ 15 , 19 , 20 ]. Our study revealed that most information provided originates from nonacademic, nongovernment sources (72.2%), with 21.5% from social media websites.…”
Section: Discussionmentioning
confidence: 99%